A necessary role for increased biglycan expression during L1‐mediated colon cancer progression - Saha, Arka; Cheriyamundath, Sanith; Kumar, Anmol; Gavert, Nancy; Brabletz, Thomas; Ben‐ze’ev, Avri (International Journal of Molecular Sciences, 2022)
Aberrant activation of Wnt/β‐catenin signaling and downstream β‐catenin‐TCF target genes is a hallmark of colorectal cancer (CRC) development. We identified the immunoglobulin‐like cell adhesion receptor L1CAM (L1) as a target of β‐catenin‐TCF transactivation in CRC cells. Overexpression of L1 in CRC cells confers enhanced proliferation, motility, tumorigenesis, and liver metastasis, and L1 is exclusively localized at invasive areas of human CRC tissue. Several genes are induced after L1 transfection into CRC cells by a mechanism involving the L1‐ezrin‐NF‐κB pathway. We conducted a secretomic analysis of the proteins in the culture medium of L1‐overexpressing CRC cells. We detected a highly increased level of biglycan, a small leucine‐rich ECM component, and a signaling molecule. We found that induction of biglycan is required for the cellular processes conferred by L1, including enhanced proliferation, motility, tumorigenesis, and liver metastasis. The suppression of endogenous biglycan levels or a point mutation in the L1 ectodomain that regulates cell–cell adhesion mediated by L1 blocked the enhanced tumorigenic properties conferred by L1. The mechanism of biglycan induction by L1 involves the L1‐NF‐κB pathway. Blocking NF‐κB signaling in L1 expressing cells suppressed the induction of biglycan and the tumorigenic properties conferred by L1. Biglycan expression was undetectable in the normal colonic mucosa, but expressed at highly increased levels in the tumor tissue, especially in the stroma. The therapeutic strategies to target biglycan expression might provide a useful approach for CRC treatment in L1‐overexpressing tumors.
CRIS-Team Scopus Importer:2022-01-07
Keywords: Biglycan; Colorectal cancer (CRC); L1CAM (L1); NF‐κB